Penerapan Metode Tasmi’ dalam Meningkatkan Kualitas Hafalan Al-Qur’an Siswa MI - Ifadah, Rifatul; Rahmah, Eka Naelia; Fatimah, Fatma Siti Nur (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
This study aims to determine the application of the Tasmi’ method in improving the quality of students memorization. This research place in school MI Mumtaza Islamic School Pondok Cabe Udik. The main data source is Head of tahfidz, Deputy Head of Curriculum, Tahfidz Teacher, and students of the class V MI Mumtaza Islamic School Pondok Cabe Udik. This research is motivated by the existence of the Tasmi’ program which is implemented in schools MI Mumtaza Islamic School. The teacher provides a special method so that students do not feel bored when memorizing the Qur’an. The method applied is the Tasmi’ method to train students in repeating rote memorization. The Tasmi’ method is a way to expedite memorization and sharpen memorization. This research method uses a descriptive qualitative approach. Data collection teachniques by interview, observation, and documentation. Data analysis used is data reduction, data display (presentation of data), and make decisions. The result of this study indicate that the implementation of the Tasmi’ program is very useful and able to improve the quality of students memorization. Even though there are many obstacles at the technical level, with the existence of this Tasmi’ program students can istiqamah in reviewing their memorization, either memorizing new material or memorizing old material.